Bacterial behaviour in the biodegradation of phenol by indigenous bacteria immobilized in Ca-alginate beads. Issue 14 (19th June 2020) - Namane, A.; Amrouche, F.; Arrar, J.; Ali, O.; Hellal, A.
ABSTRACT: The phenol biodegradation by Ca-alginate immobilized indigenous bacteria was performed in batch system. The effects of some operational parameters were evaluated, including % weight of alginate, calcium and CaCl2, diameter of spheres; jellification time; solution concentration; adaptation concentration and alginate/cells ratio. The optimal biodegradation conditions were found for 2% and 3% of weight for respectively the sodium alginate and calcium chloride. The hardening time was 30 min and beads diameter of 4 cm. The degradation efficiency of the immobilized strains in these conditions exceeds 800 mg·L −1 . The results show that the mass transfer flow (nutritional intake) which depends on the concentration gradient (dC/dz), the physical-chemical properties of alginate beads through the diffusivity coefficient (D), govern the bacterial kinetics and the spatial and temporal behaviour of bacteria. GRAPHICAL ABSTRACT: